Beamforming for relay assisted MIMO - Saand, A.S. (IGI Global, 2016)
In cellular wireless communication systems, the current and future networks are promising to provide multimedia services at the cell edges and beyond the cell boundaries efficiently and cost effectively. The relay assisted MIMO networks have got much attraction to meet the requirements by providing high capacity, link reliability and high quality of service. The performance of the relay assisted networks is maximized by making the use of beamforming design at the relay nodes. This chapter describes the recent developments in relay beamforming design for Amplify-and-Forward (AF) relay networks and introduces a new beamforming scheme to improve the network performance in terms of ergodic capacity. The chapter contributes in introduction to basic MIMO channel, various relaying strategies and introduction to relay assisted network topologies. It is followed by critical literature review on AF beamforming techniques. This leads towards the novel and efficient relay beamforming design, its performance evaluation and validity by comparing with various available beamforming techniques. Â© 2017, IGI Global.